Utilization of augmented reality technology in overcoming educational issues in Indonesia - Suharsono Bantun; Dedi Kuswandi; Saida Ulfa; Henry Praherdhiono; Jayanti Yusmah Sari; Made Duananda Kartika Degeng (Institute of Advanced Engineering and Science, 2026)
Education in Indonesia faces various challenges, including limited access to quality education, insufficient resources and infrastructure, a shortage of qualified teachers, and limited integration of technology in the learning process. Augmented reality (AR) offers a promising solution by combining real-world and virtual elements to create interactive and immersive learning experiences. This review identifies that AR enhances student engagement, improves understanding of complex concepts, and supports more accessible and personalized learning environments. AR also helps address infrastructure limitations through virtual simulations and mobile-based learning applications. However, challenges remain, including cost and sustainability issues, teacher training needs, infrastructure requirements, and internet connectivity. Therefore, strategic policies, collaboration among stakeholders, and the development of AR-based curriculum content are required to support sustainable implementation. Furthermore, emerging immersive technologies such as mixed reality (MR) offer additional opportunities for interactive learning; however, further empirical research is required to evaluate their effectiveness in Indonesian educational contexts.